12 Installationen + 1 Komposition = 13 - Schepers, Heiner; Kunstverein Lingen, Lingen (Lingen/Bergen : Buxus Verlag, 1998)
Enders, Ulrike ; Bachhuber, Liz ; Mookerjee, Lila ; Lange - Krijtenburg, Margriet ; Kessler, Susanne ; Rihs, Christoph ; Hörnschemeyer, Franka ; Hanh, Wolfgang ; Demnig, Gunter ; Boehle, Hilmar et al.
12 Installationen + 1 Komposition = 13, Kunstverein Lingen, Lingen
kunstcatalogus